The Palenque project: Evaluating interaction in an online virtual archaeology site - Champion, Erik; Bishop, I.; Dave, B. (Springer UK, 2012)
This case study evaluated the effect on cultural understanding of three different interaction modes, each teamed with a specific slice of the digitally reconstructed environment. The three interaction modes were derived from an initial descriptive theory of cultural learning as instruction, observation and action. A major aim was to ascertain whether task performance was similar to the development of understanding of the cultural context reached by participation in the virtual environment. A hypothesis was that if task performance is equivalent to understanding and engagement, we might be able to evaluate the success of virtual heritage environments (through engagement and education), without having to annoy the user with post-experience questionnaires. However, results suggest interaction in virtual heritage environments is so contextually embedded; subjective post-test questionnaires can still be more reliable than evaluating task performance.